Light Weight Complete Denture Prosthesis - A Case Report - A Khanal; IK Limbu; PK Parajuli; P Suwal; RK Singh (Journal of Gandaki Medical College, 2019)
Retention, stability and support are the basic principles on which the success of a complete denture relies on. Extreme resorption of the maxillary denture-bearing area leads to a narrower, constricted residual ridge with decreased supporting tissues and a larger restorative space between the maxillary and mandibular residual ridge. Rehabilitation in such cases may result in increased weight and height of the prosthesis further compromising its retention, support and stability. So, to prevent further resorption of ridges, the weight of the prosthesis needs to be reduced which can be achieved by making hollow prosthesis. This case report describes a novel technique of fabricating maxillary hollow maxillary complete denture.